RETRIEVAL OF BALLOON FROM RIGHT CORONARY ARTERY SURGICALLY - Shirazi, Zara; Zia, Kashif; Mahmood, Zain; Hussain, Syed Minhaj; Bughio, Hafeezullah; Saghir, Tahir; Chaudhry, Pervaiz A (Journal of Ayub Medical College Abbottabad, 2022)
Angioplasty balloon entrapment remains an infrequent but dangerous obstacle that requires forbearance and pre-built management strategies in order to avoid morbidity or worse, mortality. Here, we discuss an un-expected hurdle of an undeflated stuck balloon with fractured shaft during angioplasty of proximal right coronary artery (RCA) in a 60-year-old male which was attempted percutaneously and redeemed surgically but massive infarction to RCA territory was inevitable.